Geospatial analysis for the assessment of mine land reclamation area: a case study of Noamundi Block, Jharkhand - Maiti, Kunal Kanti; Bandyopadhyay, Jatisankar; Chakravarty, Debashish; Das, Subha; Mondal, Sonjay (Spatial information research (Online), 2019)
Reclamation consists of modifying the disturbed land and returning it to a more natural state of hills, grasslands, forests and lakes for the benefit of future generations. This study analyzed the change of land use and land cover in the Noamundi block (West Singhbhum district, Jharkhand), India. This paper demonstrates the impact of mining on the natural environment in this area by using three images of the Landsat missions from 2003, 2011 and 2017 which were processed by the supervised image classification (8 classes). By comparing the classified images this paper retrieve the absolute and relative change of land use and land cover in the study area. An accuracy assessment is performed to describe the quality of the classification. The maximum increase of agricultural areas is detected with a decrease in forest areas.